2014
DOI: 10.1016/j.neuropharm.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Predator odor stress alters corticotropin-releasing factor-1 receptor (CRF1R)-dependent behaviors in rats

Abstract: Humans with stress-related anxiety disorders exhibit increases in arousal and alcohol drinking, as well as altered pain processing. Our lab has developed a predator odor stress model that produces reliable and lasting increases in alcohol drinking. Here, we utilize this predator odor stress model to examine stress-induced increases in arousal, nociceptive processing, and alcohol self-administration by rats, and also to determine the effects of corticotropin-releasing factor-1 receptors (CRF1Rs) in mediating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 82 publications
8
28
0
Order By: Relevance
“…These data suggest that predator odor is a powerful aversive stimulus that produces similar increases in anxiety-like behavior in all stressed rats. This is in agreement with previous reports that predator odor increases anxiety-like behavior (1, 5) and startle reactivity in rats (1, 22). Other types of stress (e.g., restraint stress or footshock) also produce increases in anxiety-like behavior as measured by the EPM and open field test (3, 13).…”
Section: Discussionsupporting
confidence: 94%
“…These data suggest that predator odor is a powerful aversive stimulus that produces similar increases in anxiety-like behavior in all stressed rats. This is in agreement with previous reports that predator odor increases anxiety-like behavior (1, 5) and startle reactivity in rats (1, 22). Other types of stress (e.g., restraint stress or footshock) also produce increases in anxiety-like behavior as measured by the EPM and open field test (3, 13).…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with the current results that predator odor stress using dirty rat bedding increased subsequent ethanol consumption in male and female C57BL/6J mice, male Wistar rats increased operant responding for ethanol after exposure to predator odor stress using bobcat urine (at least in those animals which avoided the odor-paired chamber; Edwards et al, 2013; Roltsch et al, 2014). Exposure to bobcat urine also increased thermal nociception 5 days later and increased startle reactivity 2 days later (Roltsch et al, 2014), suggesting that a high arousal and high nociception state after predator odor stress may contribute to the increase in ethanol self-administration. Mice also exhibit increased anxiety after exposure to predator odor stress.…”
Section: Discussionsupporting
confidence: 92%
“…In support of this general hypothesis, limited available data in other genotypes indicate that repeated restraint stress significantly increased ethanol intake in male and significantly decreased ethanol intake in female mice that were selectively bred for high alcohol preference (HAP; Chester et al, 2006), and that tail suspension stress significantly increased ethanol intake only in female but not in male CD-1 mice with high immobility scores (Pelloux et al, 2005). Finally, because perceived predation risk has a profound biological effect across species (Zanette et al, 2011), and predator odor stress significantly increased ethanol self-administration in male Wistar rats (Edwards et al, 2013; Roltsch et al, 2014), we predicted that exposure to predator odor stress would significantly increase ethanol intake and that the effect might be more pronounced in female mice.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to nociception, both stress and intraCeA corticosterone pellet implants produce somatic hypersensitivity by increasing CRF expression in CeA, and these effects are blocked by antisense CRF knockdown in CeA (Johnson et al, 2015). Previous work by our group showed that predator odor exposure increases thermal nociception and this effect is reversed by systemic blockade of CRFR1s (Roltsch et al, 2014).…”
Section: Introductionmentioning
confidence: 86%